'Sovereignism' and the challenge of welfare reform. Pensions and social assistance between innovation, continuity and reversions to the past. Issue 2 (2nd April 2020) - Stamati, Furio
ABSTRACT: This article deals with the 'quota 100ʹ early retirement option and the "citizenship income" (Reddito di cittadinanza) social assistance scheme introduced by the Conte government early in 2019. The two programmes claim to represent a clear break with the last ten years of subtractive social policy reforms and EU-imposed austerity. We first present the key innovations before analysing them against the background of recent institutional changes. Their political logic and (early) outcomes are analysed in light of the package negotiated among the forces supporting the Government: the Five-star Movement and Matteo Salvini's League. The article then considers the reforms' likely durability, taking as a benchmark the events following the appointment of the second Conte government. With hindsight, the new policies are less radical and anti-EU than they appear at first sight, which contributes to their political sustainability.